The Impact of Teacher Power on University Students’ Satisfaction - Mustafa Rezaei; Baz Mohammad Frogh; Mujeeb Rahman Rahmani; Ali Naqi Mohammadi (Randwick International of Education and Linguistics Science Journal, 2023)
The aim of this study was to find the impact of teacher power on students’ satisfaction. Participants were 364 university students (60 girls and 304 boys) which were selected by quota-random sampling method. All the students of the research sample voluntarily completed the questionnaires about the teacher’s power and students’ satisfaction. For analyzing the research data, SPSS.v.24 software was used. Results showed that there is a significant positive relationship between student satisfaction with both referent power and expert power. In addition, According to the difference in averages, the highest Mean is related to the type of reward power and the lowest mean was related to the type of coercive power. The findings further showed that female students are more satisfied than male students and in both groups, the least satisfaction was for evaluation method. Finally, the results indicate the importance of the optimal use of various teachers' power sources by teachers in forming a favorable climate, which can play a key role in increasing the satisfaction of students.